Prevention of bone loss and management of fracture risk in HIV-infected individuals: case studies and recommendations for different patient subgroups. (June 2011) - Post, Frank A; McCloskey, Eugene V; Compston, Juliet E; Bowman, Christine A; Hay, Phillip E; Johnson, Margaret A; Mallon, Patrick WG; Peters, Barry S; Samarawickrama, Amanda; Tudor-Williams, Gareth
Increased life-expectancy and the need for long-term antiretroviral therapy have brought new challenges to the clinical management of HIV-infected individuals. While the prevalence of osteoporosis and fractures is probably increased in HIV-infected patients, optimal strategies for risk assessment and treatment in this relatively young population are yet to be defined. Prevention of bone loss is likely to become an important component of HIV care as the HIV-infected patient population grows older. In this article, we present an overview of the literature on bone loss in individuals with HIV and discuss the practical application of the European AIDS Clinical Society (EACS) guidelines to a range of clinical case scenarios.